KONSEP AL-FANA, AL-BAQA DAN AL-ITTIHAD ABU YAZID AL-BUSTAMI - Junaidin Junaidin (STIT Sunan Giri Bima, 2021)
This article is an analysis of the concepts of fana, baqa and Ittihat promoted by Abu Yazid al-Bustami. The understanding of Fana' which was developed by him is to state that when humans have reached the level of Fana', which means the loss of awareness of the existence of oneself and the environment, then he will be Baqa' which means continuous in the attributes of divinity. Namely, the eternal commendable attributes and attributes of God in humans and the peak is that humans can unite or ittihad with God so that the personal self becomes non-existent and there is only God. This understanding received mixed responses from the scholars. Shari'ah scholars or fiqh experts tend to state that this understanding is misleading and al-Bustami is said to be infidel, some consider it just a deviation and some understand that an understanding based on al-Bustami's expressions cannot be used as a guide because it was conveyed when he was not in his self-consciousness, but is subject to intuition when he is mortal', baqa', and Ittihad.